An useful complication of emergent pericardiocentesis procedure in cardiac tamponade: Case report - (:unkn) unknown (My University, 2018)
We present a case of 19 years old patient whom was admitted to emergency service with abdominal pain anddyspnea and had prodromal symptoms for about ten days. He was hypotensive, tachycardic and dyspneic. CTscan showed large amount of free peritoneal, pericardial and bilateral pleural fluid. With the diagnosis of cardiac tamponade; emergent pericardiocentesis was done with apical approach and quick hemodynamic relief wasobserved. It was understood that rapid haemodynamic response was a result of complication, characterized byincreasing of left pleural effusion.
Keywords: Kalp ve Kalp Damar Sistemi